Virial theorem and gravitational equilibrium with a cosmological constant (2001)
Starting from the Newtonian limit of Einstein's equations in the presence of a positive cosmological constant, we obtain a new version of the virial theorem and a condition for gravitational equilibrium. Such a condition takes the form ρ and gt; λρvac, where ρ is the mean density of an astrophysical system (e.g. galaxy, galaxy cluster or supercluster), λ is a quantity which depends only on the shape of the system, and ρvac is the vacuum density. We conclude that gravitational stability might be infiuenced by the presence of Λ depending strongly on the shape of the system.